A 700 GHz finline mixer with three stage stub tuning - Yassin, G; Kittara, P; Grimes, P; Withington, S; Jacobs, K (2003)
We report the successful operation of a 700 GHz SIS finline mixer employing a Nb tunnel junction and Nb transmission lines. In particular, we discuss the properties of a new mixer feed and the influence of-tuning on the mixer performance. Experimental and simulation work shows that the performance of the mixer below the superconducting gap is strongly dependent on the electrical properties of the tuning stub, while at frequencies above the gap the mixer performance is dominated by both tuning and transmission lines losses.